Personalised Medicine in Modern Era - Movafagh, Abolfazl (Asian Pacific Journal of Cancer Biology, 2016)
Personalised Medicine is a medical procedure that separates patients into different groups-with medical decisions, practices, interventions and/or products being tailored to the individual patient based on their predicted response or risk of disease. The terms personalized medicine, precision medicine, stratified medicine are used interchangeably to describe this concept.